2022
DOI: 10.3389/fcvm.2022.837270
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction: An Emerging Link in the Pathophysiology of Cardiorenal Syndrome

Abstract: The crosstalk between the heart and kidney is carried out through various bidirectional pathways. Cardiorenal syndrome (CRS) is a pathological condition in which acute or chronic dysfunction in the heart or kidneys induces acute or chronic dysfunction of the other organ. Complex hemodynamic factors and biochemical and hormonal pathways contribute to the development of CRS. In addition to playing a critical role in generating metabolic energy in eukaryotic cells and serving as signaling hubs during several vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 164 publications
(171 reference statements)
1
21
0
Order By: Relevance
“…This metabolic flux shifts are also termed energy metabolism remodeling (Razeghi et al, 2002) (Huang et al, 2020a). Growing evidences, including ours, have suggested damaged mitochondria as a vital contributor to energy metabolism remodeling in CRS (Huang et al, 2020a) (Mapuskar et al, 2019;Tirichen et al, 2021;Shi et al, 2022). Mitophagy is an essential machinery for the removal of damaged mitochondria, maintaining mitochondrial quality control and cellular homeostasis (Pickles et al, 2018).…”
Section: Metabolic Characteristics Of Crs4mentioning
confidence: 99%
See 1 more Smart Citation
“…This metabolic flux shifts are also termed energy metabolism remodeling (Razeghi et al, 2002) (Huang et al, 2020a). Growing evidences, including ours, have suggested damaged mitochondria as a vital contributor to energy metabolism remodeling in CRS (Huang et al, 2020a) (Mapuskar et al, 2019;Tirichen et al, 2021;Shi et al, 2022). Mitophagy is an essential machinery for the removal of damaged mitochondria, maintaining mitochondrial quality control and cellular homeostasis (Pickles et al, 2018).…”
Section: Metabolic Characteristics Of Crs4mentioning
confidence: 99%
“…The main pathological changes of kidney in CKD include glomerulosclerosis, tubular atrophy, interstitial fibrosis and inflammatory cell infiltration ( Webster et al, 2017a ; Wang X. H. et al, 2022 ), while a growing body of evidence observes cardiac interstitial fibrosis, cardiomyocyte hypertrophy, and mitochondrial swelling and damage in the heart ( Bigelman et al, 2018 ). Of note, mitochondrial injury has been identified as the common pathological change in both kidney and heart in the state of CKD ( Shi et al, 2022 ). Recent studies have reported that modulating mitophagy may reverse the above pathological changes in the injured kidney and heart through eliminating damaged mitochondria and maintaining mitochondrial homeostasis ( Quiles and Gustafsson, 2022 ), hinting that mitophagy might link these pathological changes between the heart and kidney.…”
Section: Mitophagy In Cardiorenal Syndrome Typementioning
confidence: 99%
“…The natriuretic peptide system (NPS) and RAAS function as opposing regulators in maintaining kidney and cardiovascular homeostasis ( Peoples et al, 2019 ). The paracrine effect of RAAS and NPS is also associated with salt and water homeostasis through the kidney ( Peoples et al, 2019 ; Shi et al, 2022 ). Three natriuretic peptides central to the NPS, atrial (ANP), and brain (BNP), as well as another non-natriuretic protein C-type natriuretic peptide (CNP), act as counter-regulators to the RAAS activities ( Ronco et al, 2012a ; Peoples et al, 2019 ).…”
Section: Pathophysiology Of Acute Crsmentioning
confidence: 99%
“…This pathologic process is referred to as cardiorenal syndrome type 4 (CRS4) (Shi et al, 2022). In these patients, the estimated glomerular filtration rate (eGFR) declines greatly, while the mortality rate resulting from heart failure (HF) increases from 56% to 131% (Thompson et al, 2015;Wheeler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10%–47% of CKD patients undergo pathologic cardiac remodeling, such as diastolic dysfunction and left ventricular hypertrophy, which can result in death. This pathologic process is referred to as cardiorenal syndrome type 4 (CRS4) (Shi et al, 2022). In these patients, the estimated glomerular filtration rate (eGFR) declines greatly, while the mortality rate resulting from heart failure (HF) increases from 56% to 131% (Thompson et al, 2015; Wheeler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%